Catecholamine-Stimulated Growth of Aeromonas hydrophila Requires the TonB2 Energy Transduction System but Is Independent of the Amonabactin Siderophore - Dong, Yuhao; Liu, Jin; Pang, Maoda; Du, Hechao; Wang, Nannan; Awan, Furqan; Lu, Chengping; Liu, Yongjie (Frontiers in Cellular and Infection Microbiology, 2016)
The growth-stimulating effects of catecholamine stress hormones have been demonstrated in many pathogens. However, catecholamine-induced growth and its underlying mechanisms remain poorly understood in Aeromonas hydrophila. The present study sought to demonstrate that norepinephrine (NE), epinephrine (Epi), dopamine (Dopa) and L-dopa stimulate the growth of A. hydrophila in iron-restricted media containing serum. NE exhibited the strongest growth stimulation, which could be blocked by adrenergic antagonists. Furthermore, it was demonstrated that NE could sequester iron from transferrin, thereby providing a more accessible iron source for utilization by A. hydrophila. The deletion of the amoA gene associated with amonabactin synthesis revealed that the amonabactin siderophore is not required for NE-stimulated growth. However, the deletion of the TonB2 energy transduction system resulted in the loss of growth promotion by NE, indicating that a specific TonB-dependent outer membrane receptor might be involved in the transport of iron from transferrin. Collectively, our data show that catecholamine sensing promotes the growth of A. hydrophila in a manner that is dependent on the TonB2 energy transduction system.